Analisis Determinan Tingkat Kemiskinan Di Provinsi Jawa Barat - Ismi Zuhairah; Diana Novita; Rahayu Rahayu; Asnidar Asnidar; Ahmad Ridha (Pusat Riset dan Inovasi Nasional, 2024)
The aim of this research is to analyze the determinants of poverty, including economic growth, human development index (HDI), and Gini index. in West Java province 2008-2022. The analytical method used in this research is multiple linear regression analysis. The data used in this research is secondary data and is a form of time series data. Based on the results of multiple linear analysis, economic growth has a partial positive and insignificant effect on the level of poverty in West Java province, while HDI has a partial negative and insignificant effect on poverty in West Java province and the Gini index has a partial negative and significant effect on poverty in West Java province. Simultaneously, economic growth, HDI and Gini index have a significant effect on poverty levels.